Copper-catalyzed regio- and enantioselective aminoboration of alkylidenecyclopropanes: the synthesis of cyclopropane-containing β-aminoalkylboranes. Issue 30 (22nd March 2016) - Jiang, Han-Chun; Tang, Xiang-Ying; Shi, Min
Abstract : A Cu-catalyzed aminoboration of alkylidenecyclopropanes with B2 pin2 and hydroxylamines produced cyclopropane-containing β-aminoalkylboranes in moderate to good yields. Abstract : A Cu-catalyzed regio- and enantioselective aminoboration of alkylidenecyclopropanes (ACPs) with bis(pinacolato)-diboron (B2 pin2 ) and hydroxylamines has been described in this paper, affording the corresponding cyclopropane-containing β-aminoalkylboranes in good yields under mild conditions. Moreover, a catalytic asymmetric variant of this transformation has also been realized by using a copper complex with a( S )-BINAP ligand along with further transformation of the product to give cyclopropane-containing 1, 2-aminoalcohols.